1997
DOI: 10.1152/jn.1997.77.3.1526
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Voltage-Activated Ca2+ Currents in Acutely Isolated Human Hippocampal Granule Cells

Abstract: Properties of Ba2+ currents through voltage-dependent Ca2+ channels (IBa) were investigated in 61 dentate granule cells acutely isolated from the resected hippocampus of nine patients with therapy-refractory temporal lobe epilepsy (TLE). Currents with a high threshold of activation (HVA) peaked at 0 mV, and showed some time-dependent inactivation and a voltage of half-maximal steady-state inactivation (V1/2inact) of -16.4 mV. Application of saturating doses of omega-conotoxin (omega-CgTx) GVIA or nifedipine di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
1
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 42 publications
3
22
1
1
Order By: Relevance
“…Likewise, results from binding studies provide evidence that PHT can interact with nifedipine-sensitive Ca2+ channels (36)(37)(38). Interestingly, the amount of the maximal PHT-mediated inhibition of HVA currents obtained in our study is comparable to the fraction of N-type Ca2+ current found in human hippocampal granule cells (24). Whether PHT partially antagonizes L-type Ca2+ current, as was shown by Miyazaki et al in glucagon-secreting tumor cells (39), or completely blocks N-type Ca2+ current will be subject of further investigations.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Likewise, results from binding studies provide evidence that PHT can interact with nifedipine-sensitive Ca2+ channels (36)(37)(38). Interestingly, the amount of the maximal PHT-mediated inhibition of HVA currents obtained in our study is comparable to the fraction of N-type Ca2+ current found in human hippocampal granule cells (24). Whether PHT partially antagonizes L-type Ca2+ current, as was shown by Miyazaki et al in glucagon-secreting tumor cells (39), or completely blocks N-type Ca2+ current will be subject of further investigations.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies in our laboratory demonstrated that dentate granule cells from adult human hippocampus express mainly high-voltage activated (HVA) Ca" currents including L-and N-type currents (24), whereas there has been no evidence for low-voltage-activated (LVA) Ca2+ currents. In this study, we examined the effects of PHT, CBZ, and GBP on HVA currents.…”
Section: Ca2+ Channels In Human Hippocampal Dentate Granule Cellsmentioning
confidence: 90%
“…While in guinea-pig DGGCs at least four different ICa components (T, L, N and P) were demonstrated (Eliot & Johnston, 1994), under our experimental conditions the predominant source of Ca¥ influx into dissociated human granule cells is a HVA ICa composed of up to three Ca¥ conductances. Our recordings also differ from those of Beck et al (1997b) in the substantially smaller peak IBa densities (60 ± 6 pA pF¢ versus the 144·3 ± 24·3 pA pF¢ in their report). This difference may stem from their use of 10 mÒ intracellular EGTA, thereby possibly lowering resting [Ca¥] and consequently basal Ca¥-dependent inactivation (see below).…”
Section: Resultscontrasting
confidence: 79%
“…Therefore, the primary utility of drugs effective in these screens would probably be against secondary generalization of seizures. However, it is clear from the studies described above and studies describing alterations in excitatory amino acid receptors (60)(61)(62)77) and other ion channels (64,(78)(79)(80) in focal tissue within the epileptic brain that many ion channels and receptors in these critical epileptogenic sites are fundamentally different from those in control tissue. Future efforts targeting these "epileptic" ion channels may have therapeutic benefit in controlling initiation of seizures rather than seizure spread.…”
Section: "Epileptic" Ion Channels: Implications For Drug Development mentioning
confidence: 99%